2021
DOI: 10.1186/s41077-020-00152-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the transvaginal ultrasound simulation training (TRUSST) programme for obstetric registrars

Abstract: Background Transvaginal ultrasound (TVUS) training opportunities are limited due to its intimate nature; however, TVUS is an important component of early pregnancy assessment. Simulation can bridge this learning gap. Aim To describe and measure the effect of a transvaginal ultrasound simulation programme for obstetric registrars. Materials and methods The transvaginal ultrasound simulation training (TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Our small pilot study clearly demonstrates the potential efficiency of a high-fidelity simulator, for improving the clinical performance and confidence of the participants in accomplishing sonographic techniques on real patients, regarding assesment of uterine cervix in pregnant woman. This corresponds with the findings of Byford et al [9] study when even unexperienced trainees had an increase in confidence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our small pilot study clearly demonstrates the potential efficiency of a high-fidelity simulator, for improving the clinical performance and confidence of the participants in accomplishing sonographic techniques on real patients, regarding assesment of uterine cervix in pregnant woman. This corresponds with the findings of Byford et al [9] study when even unexperienced trainees had an increase in confidence.…”
Section: Discussionsupporting
confidence: 92%
“…Historically ultrasound methods have been taught by hands-on practical manner training on patients or volunteers, but ethical issues of multiple unnecessary vaginal scans in gynecologic settings and As Low As Reasonably Achievable (ALARA) principle in obstetrics make these clinical training approaches less relevant. Moreover, the learning ability of the trainees, their pace of assimilating and incorporating knowledge and practical competence are very variable in such a setting [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study of twenty-four participants limited perception to questionnaire analysis [14]. Another study of 15 doctors, showed improved confidence, more systematic approach and documentation [16] but also limited perceptions to questionnaire analysis. A similar study reported questionnaire responses from 28 participants following a four hour TVUS simulation course, showing that participants believed that simulation training applied to clinical practice and that their performance would improve after simulation training [15]; a final study of medical students showed enhanced clarity and knowledge following TVUS simulation training [17].…”
Section: Discussionmentioning
confidence: 99%
“…Of the publications to date that studied trainee's perspectives of TVUS simulation training, most are quantitative studies using questionnaires or self-assessed confidence scores [10,[13][14][15][16][17] with one mixed methods study [12]. In contrast, qualitative research allows use of open-ended questions that aim to explore what is important to the trainee themselves.…”
Section: Introductionmentioning
confidence: 99%
“…OSAUS scale was used as an assessment tool during the implementation of a simulation training in emergent Focused Abdominal Sonography in Trauma (eFAST) [ 22 ] and in transvaginal ultrasound [ 44 ]. The scale was also able to discriminate competence group with a good reliability in the assessment of point-of-care ultrasonography.…”
Section: Discussionmentioning
confidence: 99%